Insects found in birds’ nests from Argentina. Myiopsitta monachus (Boddaert, 1873) [Aves: Psittacidae], exclusive host of Psitticimex uritui (Lent & Abalos, 1946) (Hemiptera: Cimicidae) - Turienzo, Paola; Iorio, Osvaldo Di (Zootaxa, 2011)
Insects in communal nests of the monk parakeet, Myiopsitta monachus [Aves: Psittacidae] were studied in Argentina (provinces of Chaco, Catamarca, La Rioja, Córdoba, Santa Fe, San Juan, San Luis, La Pampa, and Buenos Aires). A total of 176 species of insects (8 orders, 48 families) was represented by 106,556 specimens. Hemiptera was represented by 58,915 exx. (52.3%); followed by Coleoptera, 46,764 exx. (43.8%). The insects are discriminated by functional guilds and the time of residence inside the nests. Other dead insects and arthropods, inquiline insects, and birds also found in the nests are also provided.